2008
DOI: 10.1007/s11224-008-9353-4
|View full text |Cite
|
Sign up to set email alerts
|

First examples of the cocrystallization of diastereomers of chiral phosphorus compounds

Abstract: The first three examples of the cocrystallization of covalent diastereomers of phosphorus compounds containing different chiral elements (centres of chirality on carbon and phosphorus, and an axis of chirality) are reported. The phenomenon can be attributed to the complementarity of the molecular shapes of the diastereomers. The X-ray data of all the crystals exhibit centrosymmetric statistics regardless of their very different natures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Such cocrystallizations of stereoisomeric or isosteric structures with covalently connected stereogenic centers (¼ 6 ionic pairs) [19] as quasi-racemates are rare among organic compounds: the observed disorder suggests a random statistical distribution of the (R,R), (S,S) and (R,S) isomers, by analogy to (R) and (S) enantiomers in pseudo-racemates. [20] [18] Thermal ellipsoids at the 30 % probability level. For clarity, unnecessary hydrogen atoms and solvent molecules (for 1 and 2) are omitted (for details see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cocrystallizations of stereoisomeric or isosteric structures with covalently connected stereogenic centers (¼ 6 ionic pairs) [19] as quasi-racemates are rare among organic compounds: the observed disorder suggests a random statistical distribution of the (R,R), (S,S) and (R,S) isomers, by analogy to (R) and (S) enantiomers in pseudo-racemates. [20] [18] Thermal ellipsoids at the 30 % probability level. For clarity, unnecessary hydrogen atoms and solvent molecules (for 1 and 2) are omitted (for details see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In the structure of the carbo ‐dihydobarrelene 10 b , a disorder was observed due to the presence in the crystal of three stereoisomers, cis ‐ 10 b , ( R )‐ and ( S )‐ trans ‐ 10 b . Such co‐crystallizations of stereoisomeric or isosteric structures with covalently connected stereogenic centers (≠ ionic pairs) [19] as quasi ‐racemates are rare among organic compounds: the observed disorder suggests a random statistical distribution of the ( R , R ), ( S , S ) and ( R , S ) isomers, by analogy to ( R ) and ( S ) enantiomers in pseudo ‐racemates [20] …”
Section: Resultsmentioning
confidence: 99%
“…This was in fact a rather surprising result, since the co-crystallisation of covalent diastereomers is reportedly a rare occurrence. [19] With the single resorcinarene diastereomers obtained in sufficient quantities, the camphorsulfonate groups were removed by simple base-catalysed hydrolysis. [18] The six camphorsulfonate diastereomers were hydrolysed via these conditions to smoothly furnish the corresponding target single enantiomers in good to quantitative yields without needing formal purification (Scheme 6).…”
Section: Eurjocmentioning
confidence: 99%
“…Because it is important to understand the crystallization behavior of chiral compounds, Alfonsov et al [280] reported the first three examples of the cocrystallization of covalent diastereomers of phosphorus compounds. Centrosymmetric statistics were obtained for the X-ray data for all of the crystals.…”
Section: Issuementioning
confidence: 99%